Hello There! The answer is 12w - 12y + 3.
Here's a step by step on how to solve 3(2w-4y+3)+6w-6.
Step 1: Multiply the 3 by the numbers in the parenthesis.
3(2w-4y+3)+6w-6 ⇒ 6w - 12y + 9 + 6w - 6
Step 2: Rearrange the numbers so like terms are next to each other.
6w - 12y + 9 + 6w - 6 ⇒ 6w + 6w - 12y - 6 + 9.
Step 3: Combine like terms. (6w + 6w and - 6 + 9).
6w + 6w - 12y - 6 + 9 ⇒ 12w - 12y + 3
This is your final answer since you cannot simplify any further. I hope this helps and have a great day!